(untitled) (Plant Tissue Culture and Biotechnology, 2022)
An efficient and rapid in vitro regeneration protocol was developed for chrysanthemum (Chrysanthemum morifolium Ramat) using two local varieties of Bangladesh namely, BARI Chrysanthemum-2 (BARI Chry-2) and local yellow (Y). MS medium supplemented with nine different concentrations and combinations of BAP and IAA was employed to optimize regeneration protocol using young in vitro derived leaf explants. Direct organogenesis was observed from the leaf explants on MS medium supplemented with 0.5 mg/l BAP and 2.0 mg/l IAA (T6) for both the varieties. This treatment (T6) induced shoot buds directly on the adaxial surface of the leaf providing the highest regeneration percentage (90% for BARI Chry-2 and 94.73% for Y), the highest number of shoot/explant (7.6 for BARI Chry-2 and 8.6 for Y) and maximum length of the shoot after six weeks (3 cm for BARI Chry-2 and 2.9 cm for Y) of culture. Explants with initially regenerated shoots were subculture on hormone free MS medium for shoot elongation after 4 weeks of their inoculation. During elongation of shoots, 90-95% of the regenerated shoots produced roots spontaneously in hormone free MS medium within 7-8 weeks of their inoculation. Rooted plantlets were transplanted to the field following hardening where 100% plantlets were survived and produced flower without any variation. Plant Tissue Cult. & Biotech. 31(2): 161-171, 2021 (December)